Gadolinium-based coronary angiography in a patient with prior known anaphylaxis to iodine-based dye - Nirmal Guragai; Sherif Roman; Rahul Vasudev; Upamanyu Rampal; Preet Randhawa; Fayez Shamoon; Hartaj Virk; Mahesh Bikkina; JW Moses; Apurva Motivala (Greater Baltimore Medical Center, 2021)
Gadodiamide is a gadolinium-based chemical element that is considered safe and well tolerated in patients without renal dysfunction and is therefore routinely used as a contrast agent in magnetic resonance imaging. Although radio-opaque, it is not frequently used for coronary angiography due to its less than optimal image quality and prohibitive cost. Our center's previous experience was less than satisfactory but the addition of a power injection system yielded good quality diagnostic images. We report a case of 63 years old male with a known history of severe, life-threatening anaphylactic reaction to previous iodinated dye presenting with persistent angina despite optimal medical therapy. Coronary and bypass graft angiography was performed using 24 cc of undiluted Gadodiamide (OMNISCAN) with a power injector (ACIST®) without any incidents or premedication with an interpretable angiogram.